Roman, Sarmatian and Hunnish saddles - ński, Radosław (Balcanica Posnaniensia. Acta et studia, 2007)
The article addresses the origins and functionality of equestrian constructions used in antiquity and the early Middle Ages, focusing on Roman saddles with horns. The aim of the text is to explain the origins of these constructions, their connection with the traditions of nomadic peoples, and to assess their significance for the development of heavy cavalry and mounted archers. The author rejects the one-sided attribution of this invention to the Celts, pointing to strong links with the steppe environment, especially with the Sarmatian-Parthian circle. The analysis is based on archaeological sources (including finds from Valkenburg, Rottweil, Vindolanda and Pazyryk), iconographic sources (reliefs, tomb depictions, Persian and Parthian art monuments) and written sources (including Josephus and Fronton). An important methodological element is the reconstruction of saddles and experiments with their use, which allowed for the verification of hypotheses concerning their functionality. The conclusions indicate that Roman ‘horned’ saddles were created as a result of the synthesis of sedentary and nomadic traditions, and their design was closely related to the needs of heavily armed cavalry and horse archers. The evolution of these solutions is part of a broader process of military change at the turn of the era, leading to the dominance of armoured cavalry in the armies of the ancient world.